2014
DOI: 10.1161/circgenetics.113.000324
|View full text |Cite|
|
Sign up to set email alerts
|

Desensitization of Myofilaments to Ca 2+ as a Therapeutic Target for Hypertrophic Cardiomyopathy With Mutations in Thin Filament Proteins

Abstract: Background Hypertrophic cardiomyopathy (HCM) is a common genetic disorder caused mainly by mutations in sarcomeric proteins and is characterized by maladaptive myocardial hypertrophy, diastolic heart failure, increased myofilament Ca2+ sensitivity and high susceptibility to sudden death. We tested the following hypothesis: correction of the increased myofilament sensitivity can delay or prevent the development of the HCM phenotype. Methods and Results We used an HCM mouse model with an E180G mutation in α-tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
68
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 61 publications
6
68
0
Order By: Relevance
“…Based on the current computational models, we and others have designed engineered cTnC variants with altered Ca 2+ binding affinities (to cTn) and demonstrated that those variants alter the contractile function in cardiomyocytes and correct or prevent disease-related aberrant Ca 2+ binding and contractile function [163, 187, 188, 203-209]. These studies also provide important implications with respect to the design of Ca 2+ sensitizing or desensitizing small molecules or drugs.…”
Section: Summary and Future Directionsmentioning
confidence: 85%
“…Based on the current computational models, we and others have designed engineered cTnC variants with altered Ca 2+ binding affinities (to cTn) and demonstrated that those variants alter the contractile function in cardiomyocytes and correct or prevent disease-related aberrant Ca 2+ binding and contractile function [163, 187, 188, 203-209]. These studies also provide important implications with respect to the design of Ca 2+ sensitizing or desensitizing small molecules or drugs.…”
Section: Summary and Future Directionsmentioning
confidence: 85%
“…These results suggest that the R204 residue is important in cTnI function and that increased Ca 2+ sensitivity may be a major factor in HCM. The increase in myofilament sensitivity to Ca 2+ is important since reduction in the Ca 2+ sensitivity was found to prevent the development of HCM (Alves et al, 2014). Others have suggested that increased Ca 2+ -sensitivity is associated with HCM (Wei and Jin, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…77 In support of this idea, normalization of Ca 2+ sensitivity of tension in a mouse model of HCM prevented the development of HCM in one study. 78 The authors concluded that myofilament desensitization to Ca 2+ could be a therapeutic target for treatment of HCM. While this approach could be widely applicable in principle, it is still likely to be a vast oversimplification considering the heterogeneity that underlies HCM.…”
Section: Human Hcmmentioning
confidence: 99%